A case of pubic abscess after prostate cancer surgery and radiotherapy treated with rectus femoris muscle flap. (December 2020) - Senda, H.; Okamoto, H.
Summary: We report the case of a 95-year-old man with soft tissue deficiency associated with a pubic abscess that occurred 30 years after prostate cancer surgery and radiation therapy. A fistula with purulent discharge without any obvious cause appeared in the midline of the lower abdomen and progressed to a soft tissue defect in which several calcium phosphate stones of 5-8 mm in diameter were found. Computed tomography showed calcium deposits on the surface of the pubis and irregular zonal calcifications extending from the pubis to the medial region of both thighs. Conservative treatment did not improve the patient's condition; thus, surgical treatment was performed. The pedicled rectus femoris muscle flap was elevated from the left thigh and transferred to fill the tissue defect, then a split thickness skin graft was applied on it. The tissue defect was successfully repaired, and the patient was able to regain ambulation ability. In the present case, it was presumed that urine exudation around the bladder due to radiation cystitis was involved in the formation of ectopic calculi and subsequent infection. In reconstructing a complex defect associated with infection, using muscle flaps to fill the dead space with well vascularized tissue is considered to be appropriate. In our case, we chose a rectus femoris muscle flap, which has advantages in volume and versatility of transposition owing to long vascular pedicle and requires no microsurgical vascular anastomosis. As a result, the preoperative activity was maintained, the infection was treated, and a good course was obtained.